Effects of Backpack Load and Trekking Poles on Energy Expenditure During Field Track Walking - Brito, João (2018)
This study evaluates the eﬀects of the use of backpack load and trekking poles on feld track walking energy expenditure. Twenty male volunteer pole walkers (age: 22.70 ± 2.89 years; body mass: 77.90 ± 11.19 kg; height: 1.77 ± 0.06 m; percentage of body fat: 14.6 ± 6.0 %) walked at a self-selected pace on a pedestrian feld track over a period of more than six months. Each subject was examined at random based on four walking conditions: non-poles and non-load, with poles and non-load, nonpoles and with load, with poles and with load. Heart rate, oxygen uptake and energy expenditure were continuously recorded by a portable telemetric system. Non-load walking speed was lower during walking with poles when compared with no poles (p ≤ 0.05). Oxygen uptake, energy expenditure and heart rate varied signifcantly across diﬀerent conditions. Our results suggest that the use of trekking poles does not inﬂuence energy expenditure when walking without an additional load, but it can have an eﬀect during backpack load walking. Moreover, our results indicate that the use of trekking poles may not be helpful to lower the exertion perceived by the subjects when walking with an additional load.